Immunopathological aspects of hashimoto's thyroiditis (International Seven Journal of Health Research, 2023)
Hashimoto's thyroiditis, or chronic lymphocytic thyroiditis, is an autoimmune disease, whose main feature is inflammation of the thyroid gland, resulting from an error in the immune system. In this disease, the body produces antibodies against thyroid cells that cause the destruction or loss of function of the gland. This study aims to conduct an integrative review to describe the current state of knowledge about the immunopathological process involved in Hashimoto's thyroiditis (HT), so that the research focused on understanding the immune response triggered in HT. It also aims to clarify its pathophysiology and its importance in understanding the exacerbated response of the body to this autoimmune disease. This is a bibliographic review using indexed articles available in full for free, published between 2019 and 2023, in the U.S. National Library of Medicine (NLM), Google Scholar and Scientific Electronic Library Online (SCIELO).